The Absorption of Nanomaterial Thin Films at Liquid /Liquid Interface - Enteisar M. Albrasi (Journal of Pure & Applied Sciences, 2020)
Nanomaterial refers to materials whose exist at the nanometer scale. The behaviour and the properties of nanomaterials as films at the interfaces between two immiscible liquids have extensively been studied in recent years and is of considerable importance in electronic and optoelectronic fields involving the applications for the generation of solar energy. The development of this technique has made its technology a fertile area for scientific research. The growth and ordering of Nano films at the interfacial region have made this new strategy more attractive. Generally, a thin film of nanomaterial's is small thicknesses created by wet chemical method. By this, a simple method gold and cadmium sulphide thin films of nanocrystals have been prepared. In this work, we report the results of our study on a thin film of gold nanocrystals at room temperature and CdS nanocrystals thin film at 40°C adhered at the interfacial region between two immiscible liquids. By using an easily useful experimental technique such as UV-vis Double Beam spectrophotometer films were investigated.